Integrity of swamp buffalo sperm on a variety of semen freezing process - Herdis .; B Purwantara; I Supriatna; I.G Putu (Indonesian Center for Animal Research and Development (ICARD), 1999)
Sperm of swamp buffalo bulls is easily damaged during freezing process. Acrosomal intact and plasma membrane intact is important factors in fertilization process. This experiment was aimed to study the effect of freezing method on sperm integrity. The result of experiment indicated that the mean of intact acrosomal and the intact plasma membrane for 4 hours of equilibration (52.24 ± 3.70% and 54.34 ± 4.80%) was significant higher (P<0.05) than 2 hours of equilibration (39.00 ± 3.32% and 43.44 ± 4.91%) but was not significantly difference (P>0.05) with 6 hours of equilibration (47.92 ± 4.51% and 51.58 ± 4.25%). There were not significance difference between one step and two step of glycerolization. The best sperm integrity was resulted by freezing method with 4 hours of equilibration and two steps glicerolization. Key words : Swamp buffalo bulls, sperm integrity, freezing process